Neutron Radiation Dose Measurements in a Scanning Proton Therapy Room: Can Parents Remain Near Their Children During Treatment? - Mares, Vladimir; Farah, Jad; De Saint-Hubert, Marijke; Domański, Szymon; Domingo, Carles; Dommert, Martin; Kłodowska, Magdalena; Krzempek, Katarzyna; Kuć, Michał; Martínez-Rovira, Immaculada; Michaś, Edyta; Mojżeszek, Natalia; et al. (Frontiers in Oncology, 2022)
Purpose This study aims to characterize the neutron radiation field inside a scanning proton therapy treatment room including the impact of different pediatric patient sizes. Materials and Methods Working Group 9 of the European Radiation Dosimetry Group (EURADOS) has performed a comprehensive measurement campaign to measure neutron ambient dose equivalent, H*(10), at eight different positions around 1-, 5-, and 10-year-old pediatric anthropomorphic phantoms irradiated with a simulated brain tumor treatment. Several active detector systems were used. Results The neutron dose mapping within the gantry room showed that H*(10) values significantly decreased with distance and angular deviation with respect to the beam axis. A maximum value of about 19.5 µSv/Gy was measured along the beam axis at 1 m from the isocenter for a 10-year-old pediatric phantom at 270° gantry angle. A minimum value of 0.1 µSv/Gy was measured at a distance of 2.25 m perpendicular to the beam axis for a 1-year-old pediatric phantom at 140° gantry angle. The H*(10) dependence on the size of the pediatric patient was observed. At 270° gantry position, the measured neutron H*(10) values for the 10-year-old pediatric phantom were up to 20% higher than those measured for the 5-year-old and up to 410% higher than for the 1-year-old phantom, respectively. Conclusions Using active neutron detectors, secondary neutron mapping was performed to characterize the neutron field generated during proton therapy of pediatric patients. It is shown that the neutron ambient dose equivalent H*(10) significantly decreases with distance and angle with respect to the beam axis. It is reported that the total neutron exposure of a person staying at a position perpendicular to the beam axis at a distance greater than 2 m from the isocenter remains well below the dose limit of 1 mSv per year for the general public (recommended by the International Commission on Radiological Protection) during the entire treatment course with a target dose of up to 60 Gy. This comprehensive analysis is key for general neutron shielding issues, for example, the safe operation of anesthetic equipment. However, it also enables the evaluation of whether it is safe for parents to remain near their children during treatment to bring them comfort. Currently, radiation protection protocols prohibit the occupancy of the treatment room during beam delivery.